Simulating flood risk under non-stationary climate and urban development conditions – Experimental setup for multiple hazards and a variety of scenarios. (April 2018) - Löwe, Roland; Urich, Christian; Kulahci, Murat; Radhakrishnan, Mohanasundar; Deletic, Ana; Arnbjerg-Nielsen, Karsten
Abstract: A framework for assessing economic flood damage for a large number of climate and urban development scenarios with limited computational effort is presented. Response surfaces are applied to characterize flood damage based on physical variables describing climate-driven hazards and changing vulnerability resulting from urban growth. The framework is embedded in an experimental setup where flood damage obtained from combined hydraulic-urban development simulations is approximated using kriging-metamodels. Space-filling, sequential and stratified sequential sampling strategies are tested. Reliable approximations of economic damage are obtained in a theoretical case study involving pluvial and coastal hazards, and the stratified sequential sampling strategy is most robust to irregular surface shapes. The setup is currently limited to considering only planned urban development patterns and flood adaptation options implemented over short time horizons. However, the number of simulations is reduced by up to one order of magnitude compared to scenario-based methods, highlighting the potential of the approach. Highlights: Flood damage is conceptualized as function of variables for hazard and vulnerability. Resulting response surfaces account for pluvial and costal hazard and urban growth. An experimental setup based on kriging and sequential sampling is proposed. Flood risk can be quantified reliably using this setup. Significantly fewer detailed simulations are needed for flood risk assessment.